Dose-dependent effects of CuO nanoparticles on germination and early seedling growth in Prunus avium - Özel, Halil Barış; Koc, Ismail; Yıldız, Yafes; Sevik, Hakan; Yıldız, Yafes; Özel, Halil Barış (Inst Forestry Lrcaf, 2025)
Nanoparticle pollution results from the release of nanoparticles into the environment, which are widely used in many areas today. For this reason, studies on nanoparticle pollution have gained significant momentum in recent years. However, studies on the effects of nanoparticle pollution on forest ecosystems and forest trees are restricted. The current study aimed to reveal the effects of copper oxide (CuO) nanoparticles, which are known for their high toxicity compared to other metal oxide nanoparticles, on the seed germination and seedling traits of Prunus avium. Seeds from 15 geographically diverse Turkish populations were treated with CuO nanoparticle solutions at five concentrations (200, 400, 600, 800, and 1,000 mg/L) to evaluate nanoparticle effects. Multiple growth parameters were quantified, including germination success (rate and percentage), radicle dimensions (length and thickness), and plumule elongation. The study results reveal that CuO nanoparticle applications affect all characters except the germination rate. Generally, germination and seedling traits are positively affected at low nanoparticle doses. However, with increasing doses, the parameters begin to decrease, and when using nanoparticles in high doses, a decrease is observed that can exceed 25% compared to the control group. In addition, it was found that there was a significant decline in both germination characteristics and seedling development as the dose increased after exceeding a certain dose level (400 and 600 mg/L). Significant differences were also found among seed populations. The lowest values for most parameters were recorded in the populations of Karab & uuml;k/Yenice and Bolu/ Mudurnu, whereas the highest ones were observed in the populations of Tekirda & gbreve;/& Scedil;ark & ouml;y, & Ccedil;anakkale/Lapseki, and Kocaeli/Kefken, Turkey.
Keywords: Copper Oxide; Germination; Nanoparticle Pollution; Prunus Avium; Seedling